2000
DOI: 10.1111/j.1741-3737.2000.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reported Influence of Research Participation on Premarital Relationships

Abstract: We examined the reported influence of participation in research on individuals in premarital relationships. Data were from a larger longitudinal study of 60 dating couples. We designed a questionnaire to evaluate the effects of participation. Responses to open-ended questions revealed 3 major sources of influence: attention to relationship evaluation, effects on relationship activities, and indirect or no influence. Closed-ended items yielded 2 dimensions: relationship-defining influence and relationship-evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Theories of cognition in close relationships suggest that individuals who participate in interviews may alter their relational beliefs because interaction with interviewers provides information about relationships in the same way that interactions with partners or third parties do. Interviews may have the power to alter relationship beliefs because, as previous research suggests, respondents tend to perceive interviewers as counselors or experts who have valuable knowledge about relationships (Hughes & Surra, 2000; Rubin & Mitchell, 1976). When combined with findings from previous research, theories of social cognition lead to the hypothesis that participation should have positive effects when the tendency to think or talk with the partner about the relationship is high and negative effects when these tendencies are low.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Theories of cognition in close relationships suggest that individuals who participate in interviews may alter their relational beliefs because interaction with interviewers provides information about relationships in the same way that interactions with partners or third parties do. Interviews may have the power to alter relationship beliefs because, as previous research suggests, respondents tend to perceive interviewers as counselors or experts who have valuable knowledge about relationships (Hughes & Surra, 2000; Rubin & Mitchell, 1976). When combined with findings from previous research, theories of social cognition lead to the hypothesis that participation should have positive effects when the tendency to think or talk with the partner about the relationship is high and negative effects when these tendencies are low.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggested that participation in studies actually increases awareness of relationship qualities and talk about relationships (e.g., Hughes & Surra, 2000; Rubin & Mitchell, 1976). It is unclear from these studies if participation actually prompts more thought or whether it simply reveals features of relationships that previously went unrecognized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations